PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT SUKU DAYAK KENDAWANGAN DI DESA RANGKUNG KECAMATAN MARAU KABUPATEN KETAPANG - Andari, Desti; Linda, Riza; Rafdinal, Rafdinal (Jurnal Protobiont, 2020)
Dayak Kendawangan tribe is a sub-tribe of Dayak which is spread around Kendawangan River in Rangkung Village, Marau District, Ketapang Regency. Dayak Kendawangan tribe still uses plants as traditional medicine. The purpose of this study was to determine the types of medicinal plants utilized by Kendawangan Dayak people in Rangkung Village. This research was conducted in October to December 2018. The method used was snowball with 11 respondents and conducted interviews with respondents to obtain information on traditional medicines and analyzed using qualitative and quantitative analysis. The results showed there were 52 species from 33 families, the most widely used family is Zingiberaceae (9,62 %). Part of a widely used plant is the leaves (42,18 %), while the way of processing and the use of medicinal plant is in boiled (59,61 %) and drunk (50,94 %). The most uptake of medicinal plants in the yard (47,82 %) and forest (39,13 %). The highest frequency of citation (FIC) value is Psidium guajava (54,5 %). Plant part value (PPV) and interspecific use value (IUV) of plants used in traditional medicine of Kendawangan Dayak tribe are 0.5-1 and 0.3-2, respectively.